PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN - Trias Waliningsuci; Mochammad Al Musadieq; Djamhur Hamid (FIA UB, 2017)
The objective is to analyze the influence of organizational culture on employee job satisfaction at PT. Entrepreneur Independent Bank Surabaya, to analyze the influence of leadership style on job satisfaction of employees, to analyze the effect of job satisfaction on employee performance, to analyze the influence of organizational culture on employee performance, to analyze the influence of leadership style on the performance of employees. The type of this research use explanatory research with a quantitative approach. The sample in this research amount to 87 employees and the sample use random sampling. This analysis using path analysis (path analysis) shows that organizational culture variables (X1) has a direct and significant effect on job satisfaction variables (Y1) with a path coefficient of 0.305. Leadership style variable (X2) has a direct and significant effect on job satisfaction (Y1) with a path coefficient of 0.249. Job satisfaction variable (Y1) has a direct and significant effect on employee performance (Y2) with a path coefficient of 0,472. Organizational culture variable (X1) has a direct and significant effect on employee performance (Y2) with a path coefficient of 0,449. Leadership style variable (X2) has a direct and unsignificant on employee performance (Y2) with a path coefficient of 0,138.Â